The dean of discipline - Waters, Michael, 1949- (Pitt poetry series., 2018)
In the richly musical and boldly imaginative poems of The Dean of Discipline, Michael Waters explores the confluences of the sensual and the spiritual, and renders their mysteries with precision and clarity. The title evokes the rigorous consciousness that prods the artist to deepen into his craft. Line by line, Waters delivers the passionate eloquence and intensity that distinguish his poems.